Sequential bronchoplastic lobectomies in complex treatment for synchronous bilateral multiple primary non-small cell lung cancer: a rare clinical case - O. I. Kit; D. A. Kharagezov; Yu. N. Lazutin; E. A. Mirzoyan; I. A. Leyman; S. N. Tikhonova (Южно-Российский онкологический журнал)
Today, lung cancer (LC) occupies a special place in the oncological general morbidity among the male population both in Russia and in foreign countries. Despite modern diagnostic capabilities provided for modern physicians, steadily frequent cases of triggering and exclusion are more common in patients older than 60–65 years. Surgery is the main treatment for early-stage non-small cell lung cancer (NSCLC), but as the disease progresses, unfortunately, its effectiveness decreases. The strategy of diagnosing and treating patients with one NSCLC has been developed and worked out for a long time and does not cause any difficulties, but in the presence of two or more tumors, especially when they are located in both lungs, the correct choice of therapy is determined by many additional factors. This article describes the rare use of extended bronchoplastic upper lobectomy as a surgical component of the complex treatment of a patient with bilateral synchronous NSCLC. Based on our own observational data, it can be claimed that the use of modern therapeutic principles in combination with surgical intervention allows achieving satisfactory long-term results in the treatment of patients with primary multiple NSCLC.The interest of the presented observation is based on the fact that it contains a description of a rare and unique application of sequential extended bronchoplastic upper lobectomy as a surgical component of the complex treatment of a patient with bilateral synchronous NSCLC, which we have not found analogues in the literature. We have shown that the consistent use of modern therapeutic modalities makes it possible to achieve satisfactory long-term results in the treatment of a locally advanced disease.